The AFFIRM Framework for gender-affirming care: qualitative findings from the Transgender and Gender Diverse Health Equity Study - Meg Quint; Schuyler Bailar; Alexis Miranda; Shalender Bhasin; Devin O’Brien-Coon; Sari L. Reisner (BMC Public Health)
Abstract Background Transgender, nonbinary, and gender diverse (TGD) people experience stigma in healthcare settings impacting healthcare utilization, including avoidance of care due to anticipated discrimination. Gender-affirming care refers to care for medical gender affirmation, such as gender-affirming hormones and surgery, as well as general care that affirms and respects TGD patients. This study sought to explore the experiences of TGD adults to inform gender-affirming care delivery and develop an actionable framework for practice. Methods Between May–October 2021, one-time individual in-depth interviews were conducted with 27 TGD adults receiving any healthcare in the greater Boston Massachusetts area to gather data about gender-affirming care. Interviews were semi-structured, explored prior and current experiences in healthcare and ideal gender-affirming care models, and conducted virtually via a secure Zoom platform. Analyses were conducted using immersion crystallization and reflexive thematic analysis; interview transcripts were double coded by two coders. Results Participants had a mean age of 28.5, ranging 18–45 years, and were: 7 transgender men, 6 transgender women, 8 nonbinary, 3 genderqueer, 1 agender, and 2 gender not specified. Themes about gender-affirming care coalesced into the acronym AFFIRM: (1) Affirms in individual interactions: Participants called for affirmation of TGD identity, lived expertise, and competent TGD providers and staff. (2) Flexible and accessible: Participants expressed the need for gender-affirming care to be available beyond urban population-specific clinics, in a timely fashion without long wait lists, and in a community-centered manner such as offering non-traditional times and settings. (3) Fights systemic oppression: Participants emphasized the need for providers and health systems to eliminate gatekeeping practices for gender-affirming care and create care models that resist intersecting oppressive systems such as racism and cisgenderism. (4) Interacts with community: Patients desired intentional interaction with TGD community to holistically address health and unmet gender affirmation needs. (5) Retains patients in care: Patients shared the need to collaboratively identify and problem-solve obstacles to gender-affirming care with providers and healthcare systems to optimize TGD-specific retention strategies. (6) Multidisciplinary: Patients called for interdisciplinary teams with co-located services such as primary care and mental healthcare with letter-writing for surgical care, and incorporation of peer navigators to meet the broader social, health, and well-being needs of TGD people. Conclusions Findings from this study and the AFFIRM Framework which emerged from TGD patient narratives can be applied to improve current care and set benchmarks for high-quality gender-affirming care delivery and practice.